Strategi Pemertahanan Budidayaan Rumput Laut di Era Perkembangnya Pariwisata di Nusa Lembongan sebagai Sumber Belajar IPS di SMP - I Made Ari Widiasa; I Wayan Mudana; I Wayan Kertih (Universitas Hamzanwadi, 2026)
This study aims to determine how tourism development in Nusa Lembongan affects seaweed farming activities, strategies for maintaining seaweed farming amidst increasing tourism in Nusa Lembongan, and aspects of the lives of seaweed farmers in Nusa Lembongan during the era of tourism development as a social studies learning resource in junior high schools. This study employed a descriptive qualitative approach. The data collection methods used were observation, interviews, and documentation. Data validity was checked using triangulation of data collection methods and data sources. Data analysis methods and techniques were also used, which involved several stages: data collection, data reduction, data presentation, and verification/conclusion drawing. The results show that the tourism community in Nusa Lembongan is growing rapidly, but this development has affected seaweed farming activities in Nusa Lembongan. The Nusa Lembongan community employs seaweed conservation strategies. These strategies include active strategies, passive strategies, and network strategies. These aspects of the conservation strategies of seaweed farmers in Nusa Lembongan can be used as learning resources for social studies subjects in junior high schools related to defense strategies.